If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+2m=4m+5
We simplify the equation to the form, which is simple to understand
2+2m=4m+5
We move all terms containing m to the left and all other terms to the right.
+2m-4m=+5-2
We simplify left and right side of the equation.
-2m=+3
We divide both sides of the equation by -2 to get m.
m=-1.5
| -3x+3/5+1/5=2(4-x)/5 | | -13-(3m+4)= | | (1-u)(2u-7)=0 | | x-7=(2x-4) | | -9x+6y=72 | | 1-4j=2j | | Y=cos(3x) | | 8+2(3a-5)-(6a-8b*b)-4b*b= | | 8x+4y=-56 | | 5x^2+18x-8=0 | | 2.5x+15+0.5(x-4)=1.2x+2(0.5x-6) | | 4(2y+9)+7y= | | 7(x+2)=7x+2 | | (5x+3-2)(8-2x+1)= | | 9-.333g=13 | | 2x^2+9x=5 | | .25f=8-3 | | 3(4x-3)+2x=89 | | .25f+3=8 | | 3(4x+3)=68 | | 2(x+5)-10=8 | | 4x-20=7x+14 | | 15m-2(3+5m)= | | 15x^2-50y+35=0 | | 2-(8p-q)-7(p+6)+4q= | | -8x+x^2=-12 | | x^2-x-20=0 | | 7(p+3)=7b-4 | | f(11)=1/2(11)+5 | | 9(s+7)-(7s+m)-9m= | | f(11)=2(11)+5 | | 9(7x+8)+3(x+-10)= |